2022
DOI: 10.1007/s00106-022-01208-3
|View full text |Cite
|
Sign up to set email alerts
|

Vermessung der Cochlea mittels eines Tablet-basierten Softwarepakets: Einfluss der Bildgebungsmodalität und des Untersucherhintergrunds

Abstract: Zusammenfassung Hintergrund Die Größe der Cochlea ist individuell unterschiedlich, was sich in der variablen Länge des Ductus cochlearis (CDL) ausdrücken lässt. In der Cochleaimplantatversorgung ist ein in der Länge angepasster Elektrodenträger durch eine optimale Abdeckung der Cochlea erfolgversprechend. Dazu kann die CDL auf Höhe des Corti-Organs (CDLOC) mittels eines Tablet-basierten Softwarepakets ausgemessen werden, um abgestimmt auf die Anatomie einen passenden Elektrodenträge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(58 reference statements)
0
2
2
1
Order By: Relevance
“…In contrast, the height of the cochlea H was significantly longer in the MRI scan than in the CT scan. This has already been demonstrated by Weber et al, who also found a greater width B and a small but significantly greater mean CDL by 0.89 mm in MRI-based measurements [50]. However, our study does not confirm the suspected causes for this: the missing bone signal and a lower resolution in MRI, described in the aforementioned study.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In contrast, the height of the cochlea H was significantly longer in the MRI scan than in the CT scan. This has already been demonstrated by Weber et al, who also found a greater width B and a small but significantly greater mean CDL by 0.89 mm in MRI-based measurements [50]. However, our study does not confirm the suspected causes for this: the missing bone signal and a lower resolution in MRI, described in the aforementioned study.…”
Section: Discussioncontrasting
confidence: 63%
“…However, our study does not confirm the suspected causes for this: the missing bone signal and a lower resolution in MRI, described in the aforementioned study. In our study, no consistently greater length parameters were detected in the MRI-based measurements than in the CT-based measurements, with the exception of the height H. The uniform setting of markers further outside, as described by Weber et al [50], was probably avoided in the present study by an intensive comparative training of the raters prior to the study. Since the height H is not included in the formula for calculating the CDL, greater values for the height H had no influence on the CDL, or on the length at 720 • , or on the selection of the optimal electrode array in the present study.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…As stated by Weber et al [ 43 ], the chosen imaging modality showed a statistically significant effect, with MRI measurements compared to HRCT being, on average, 0.89 mm greater for the CDL OC value. However, other authors considered the difference in measurements between MRI and CT images to be clinically insignificant [ 42 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 74%
“…B. vorhandenen und ggf. erhaltenswerten Restgehör auszuwählen [12,13]. Dabei ist die interindividuelle Streubreite erheblich, im eigenen Krankengut variierte die CDL zwischen 30,4-40,2 mm mit im Mittel 36,2 ± 1,8 mm [12].…”
Section: Individuelle Anatomie Und Elektrodenauswahlunclassified